The problem of personal identity in Ancient and Modern philosophy - Olifer, Olena (Actual Problems of Mind, 2017)
The author presents an overview of conceptions of personal identity in ancient and modern philosophy. Plato’s, Aristotle’s and Descartes’ views are outlined as preconditions for identity theory. Locke’s conception of personal identity is characterized as well as the arguments of his critics: Leibnitz, Butler and Thomas Reid